Design of robust AQM controllers for improved TCP Westwood congestion control - Mario di Bernardo; Luigi Grieco; Sabato Manfredi; Saverio Mascolo; Bart De Moor; Bart Motmans; Jan Willems; Paul Van Dooren; Vincent Blondel (MTNS 2004: Proceedings of the 16th International Symposium on Mathematical Theory of Networks and Systems, 2004)
This paper is concerned with the application of a novel robust AQM controller recently presented in the literature to TCP Westwood congestion control. The aim is twofold. Firstly we assess the performance of the scheme when applied to networks where the traffic is generated by sources controlled by Westwood TCP. Secondly, we validate the controller through numerical simulations showing that it guarantees better performance in the presence of unwanted variations of the load, the round trip time and the link capacity when compared to other existing AQM control schemes.